The Spiritual Legacy of Abū Madyan Shuʿayb: The Founder of Maghribī Ṣūfism And His Lasting Influence on Islamic Mysticism - Assadi, Jamal; Na’amneh , Mahmoud; Sindawi, Khaled (Journal of Ecohumanism, 2025)
This paper explores the life, teachings, and enduring legacy of Abū Madyan Shuʿayb ibn al-Ḥusayn al-Andalusī (509–594 AH / 1115–1198 CE), a pivotal figure in Islamic mysticism and the founder of one of the most influential Ṣūfī traditions in the Maghrib and al-Andalus. Known as "Shaykh al-Mashāyikh" (The Master of Masters) and "Muʿallim al-Muʿallimīn" (The Teacher of Teachers), Abū Madyan’s contributions to Ṣūfism are monumental. Utilizing historical and textual analysis, this study examines his early life in al-Andalus, his educational journey through Fās and the Mashriq, and his settlement in Bijāya (modern-day Algeria), where he established a spiritual legacy that impacted scholars and practitioners across the Islamic world. The paper investigates Abū Madyan’s role in the propagation of Islamic mysticism, his spiritual methodology rooted in the teachings of al-Junayd and al-Ghazālī, and his impact on subsequent Ṣūfī orders, including the Shādhilīyah and the BāʿAlawī. It also examines his theological contributions, as reflected in his writings (Anas al-Waḥīd and Nuzhat al-Murīd), and his poetic works, which offer profound insights into his mystical worldview. By analyzing historical accounts, including those of Ibn al-ʿArabī, al-Shaʿrānī, and Ibn Saʿd, the study contextualizes Abū Madyan’s spiritual philosophy within the broader landscape of Islamic mysticism. Furthermore, it highlights his influence on key figures like ʿAbd al-Salām ibn Mashīsh and Abū al-Ḥasan al-Shādhilī, and explores the integration of his teachings into North African and West African Islamic practices. By situating Abū Madyan’s contributions within their historical and spiritual context, this study enhances our understanding of his role in shaping Islamic mysticism and his enduring impact on Ṣūfī traditions worldwide.